A Very Robust AlGaN/GaN HEMT Technology to High Forward Gate Bias and Current - Bradley D. Christiansen; Eric R. Heller; Ronald A. Coutu; Ramakrishna Vetury; Jeffrey B. Shealy (Active and Passive Electronic Components)
Reports to date of GaN HEMTs subjected to forward gate bias stress include varied extents of degradation. We report an extremely robust GaN HEMT technology that survived—contrary to conventional wisdom—high forward gate bias (+6 V) and current (>1.8 A/mm) for >17.5 hours exhibiting only a slight change in gate diode characteristic, little decrease in maximum drain current, with only a 0.1 V positive threshold voltage shift, and, remarkably, a persisting breakdown voltage exceeding 200 V.